ANALISIS KEPUASAN MAHASISWA TERHADAP PENGGUNAAN APLIKASI EDLINK SEBAGAI MEDIA PEMBELAJARAN DI JURUSAN FARMASI POLTEKKES KEMENKES ACEH DENGAN MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Rahmad Zaini; M Bayu Wibawa; Desita Ria Yusian TB (Ubudiyah Indonesia University, 2025)
Abstract— The advancement of educational technology demands effective use of online learning platforms such as Edlink, particularly in health education institutions. This study aims to analyze the satisfaction level of Pharmacy Department students at Poltekkes Kemenkes Aceh regarding the Edlink application using the End User Computing Satisfaction (EUCS) approach. A quantitative descriptive method was employed, with data collected through a Likert-scale questionnaire distributed to 79 randomly selected respondents. The analysis focused on five EUCS dimensions: content, accuracy, format, ease of use, and timeliness. Results show that 67.1% of respondents